2018
DOI: 10.1002/acm2.12312
|View full text |Cite
|
Sign up to set email alerts
|

Physical validation of UFRIPSA: A rapid in‐clinic peak skin dose mapping algorithm for fluoroscopically guided interventions

Abstract: PurposeThe purpose of this study was to experimentally validate UF‐RIPSA, a rapid in‐clinic peak skin dose mapping algorithm developed at the University of Florida using optically stimulated luminescent dosimeters (OSLDs) and tissue‐equivalent phantoms.MethodsThe OSLDs used in this study were InLightTM Nanodot dosimeters by Landauer, Inc. The OSLDs were exposed to nine different beam qualities while either free‐in‐air or on the surface of a tissue equivalent phantom. The irradiation of the OSLDs was then model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In the definition of their calculation formula, Jones and Pasciak [30] did not include the scatter radiation from adjacent field. Neither does any of the reviewed software; however, it has a very limited influence [20].…”
Section: Dose Calculationmentioning
confidence: 99%
“…In the definition of their calculation formula, Jones and Pasciak [30] did not include the scatter radiation from adjacent field. Neither does any of the reviewed software; however, it has a very limited influence [20].…”
Section: Dose Calculationmentioning
confidence: 99%
“…However, using cumulative air kerma as a surrogate for PSD is limited because it is estimated without considering the height of the table, distribution of the radiation dose caused by tube angulation, attenuation by the table, and backscatter radiation [8,9,46]. Recently, skin dose mapping software have been studied vigorously and several studies have reported promising results [7,[10][11][12][13][14][15]47]. It has the advantage of providing PSD and dose map is automatically calculated considering distribution of the radiation dose without interfering with the clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature [52], there are some analyses on dosimetric outcomes. For different software applications validated on phantoms (PMMA, water or anthropomorphic phantom), the differences between calculated and measured doses range from 5% to 25% [27][28][29][32][33][34][36][37][38]. Most of these validations were performed only with a single field or in simple setups, for example using no more than four irradiation events and a limited number of beam projections, except for two recent studies that described a complete validation of their software [29,32].…”
Section: Dose Accuracymentioning
confidence: 99%
“…However, in those centers where software for skin dose map evaluation software is not available or for older equipment, K a,r and KAP remain useful PSD estimators [19]. It is possible to evaluate the PSD through different methods of direct measurements including thermoluminescent dosimeters (TLDs) [20], semiconductor dosimeters [21], MOSFETs [22] and radiochromic films procedures using offline tools such as RDM by MedSquare [29], DOSE by Qaelum [30], the DIDo system implemented in the software DOLIR [31], Skin Dose Map® tool integrated in DoseWatch® by GE Healthcare [32], em.dose from Esprimed [33,34], OpenSkin software provided by the OpenREM project [35], the UF-RIPSA algorithm developed at the University of Florida [36], the software developed by the Mayo Clinic [37], and two software (FDEIR and MC-GPU), based on Monte Carlo simulations [38]. These software can provide a dose map and the PSD value retrospectively; some of them are integrated into Radiation Dose Index Monitoring (RDIM) systems [29][30][31][32] and others are stand-alone products [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%